Syringic acid: structural elucidation and co-crystallization - Thipparaboina, Rajesh; Mittapalli, Sudhir; Thatikonda, Sowjanya; Nangia, Ashwini; Naidu, V. G. M.; Shastri, Nalini R. (Crystal Growth & Design, 2016)
Syringic acid (SYRA) is a potential antioxidant used in traditional Chinese medicine and is an emerging nutraceutical. Current reports claim its potential anti-angiogenic, anti-glycating, anti-hyperglycaemic, neuroprotective, and memory-enhancing properties in various animal models. To date, SYRA crystal structure has not been elucidated, and no crystal engineering studies have been reported. This study reports the crystal structure of SYRA for the first time along with its nicotinamide (SNCT-E) and urea (SU-EA-M) co-crystals. All forms were successfully characterized using single crystal X-ray diffraction (XRD), powder XRD, and differential scanning calorimetry. Single crystal analysis revealed that SYRA crystallized in the C2/c space group, whereas SNCT-E (2:1) and SU-EA-M (1:2) crystallized in the P21/n and Cmca space group, respectively. Novel co-crystals have shown improved solubility, modified dissolution profiles, and improved flow and compressibility. Cytotoxic effects were explored in DU145 prostate cancer cell lines for the first time, and significant enhancement in cytotoxicity by the co-crystals was observed compared to plain components. A two-fold increase in % cytotoxicity of SNCT-E was observed when compared to the corresponding physical mixture. These studies shed light on potential utility of SYRA as a coformer for various pharmaceutical applications to design synergistic and organ-protective co-crystals.

Mechanochemical synthesis of N-salicylideneaniline: thermosalient effect of polymorphic crystals - Mittapalli, Sudhir; Perumalla, D. Sravanakumar; Nangia, Ashwini (IUCRJ, 2017)
Polymorphs of the dichloro derivative of N-salicylideneaniline exhibit mechanical responses such as jumping (Forms I and III) and exploding (Form II) in its three polymorphs. The molecules are connected via the amide N-H center dot center dot center dot O dimer synthon and C-Cl center dot center dot center dot O halogen bond in the three crystal structures. A fourth high-temperature Form IV was confirmed by variable-temperature single-crystal X-ray diffraction at 180 degrees C. The behaviour of jumping exhibited by the polymorphic crystals of Forms I and III is due to the layered sheet morphology and the transmission of thermal stress in a single direction, compared with the corrugated sheet structure of Form II such that heat dissipation is more isotropic causing blasting. The role of weak C-Cl center dot center dot center dot O interactions in the thermal response of molecular crystals is discussed.
Keywords: crystal design; crystal engineering; Halogen bonding; hydrogen bonding; intermolecular interactions; materials science; mechanochemistry; polymorphism

Thermomechanical effect in molecular crystals: the role of halogen-bonding interactions - Mittapalli, Sudhir; Perumalla, D. Sravanakumar; Nanubolu, Jagadeesh Babu; Nangia, Ashwini (IUCRJ, 2017)
The design and synthesis of mechanically responsive materials is interesting because they are potential candidates to convert thermal energy into mechanical work. Reported in this paper are thermosalient effects in a series of halogen derivatives of salinazids. The chloro derivative, with higher electronegativity and a weaker inter-halogen bond strength (Cl center dot center dot center dot Cl) exhibits an excellent thermal response, whereas the response is weaker in the iodo derivative with stronger I center dot center dot center dot I halogen bonding. 3,5-Dichlorosalinazid (Compound-A) exists in three polymorphic forms, two room-temperature polymorphs (Forms I and II) and one high-temperature modification (Form III). The transformation of Form I to Form III upon heating at 328-333 K is a reversible thermosalient transition, whereas the transformation of Form II to Form III is irreversible and nonthermosalient. 3,5-Dibromo- (Compound-B) and 3-bromo-5-chloro(Compound-C) salinazid are both dimorphic: the Form I to Form II transition in Compound-B is irreversible, whereas Compound-C shows a reversible thermosalient effect (362-365 K). In the case of 3,5-diiodosalinazid (CompoundD) and 3,5-difluorosalinazid (Compound-E), no phase transitions or thermal effects were observed. The thermosalient behaviour of these halosalinazid molecular crystals is understood from the anisotropy in the cell parameters (an increase in the a axis and a decrease in the b and c axes upon heating) and the sudden release of accumulated strain during the phase transition. The dihalogen salinazid derivatives (chlorine to iodine) show a decrease in thermal effects with an increase in halogen-bond strength. Interestingly, Compound-B shows solid-state photochromism in its polymorphs along with the thermosalient effect, wherein Form I is cyan and Form II is light orange.

Rufinamide: crystal structure elucidation and solid state characterization - Salunke, Nita; Thipparaboina, Rajesh; Chavan, Rahul B.; Lodagekar, Anurag; Mittapalli, Sudhir; Nangia, Ashwini; Shastri, Nalini R. (Journal of Pharmaceutical and Biomedical Analysis, 2018)
Rufinamide (R) is a triazole derivative approved for the management of partial seizures and seizures associated with Lennox-Gastaut Syndrome, in November 2007. Crystal structure, solid state characterization, drug-excipient compatibility and solubility play a pivotal role in formulation development. This work deals with the crystal structure elucidation of R by single crystal X-ray diffraction and solid state characterization by thermal, spectroscopic and crystallographic techniques. Drug- excipient compatibility was assessed by differential scanning calorimetry (DSC). New RP-HPLC method for quantification of R was developed with improved retention time. Solubility and dissolution of drug in different media was determined. Additionally, the flow behavior of the drug was evaluated by measuring Carr's index and Hausner's ratio, while the compressibility behavior was studied using Well's protocol. R crystallized from dimethylformamide (R-DMF) was utilized for single crystal analysis. The drug crystallized in triclinic crystal system with P-1 space group. Asymmetric unit cell consists of two molecules of R held by intermolecular hydrogen bond (connected by N-H center dot center dot center dot O, which forms the catemeric chain). Analytical outcomes from DSC, thermogravimetric analysis (TGA) and powder X-ray diffraction (PXRD) revealed that the drug was present in pure crystalline form and was devoid of any polymorphic or pseudopolymorphic impurities. Influence of pH on the solubility and dissolution of R-DMF was found to be insignificant. The drug exhibited poor aqueous solubility, which was improved nearly 4.6 fold with the addition of 2% sodium lauryl sulphate (SLS). The drug exhibits poor flow and elastic compression nature. Excipients such as poly ethylene glycol (PEG) 8000, SLS, lactose monohydrate, starch and Hydroxypropyl methylcellulose (HPMC) E15 were incompatible with R-DMF as identified by thermal analysis. It is envisaged that these information regarding solid state properties of R-DMF would aid in identifying a logical path for formulation development. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Compressibility; Dissolution media; DSC; HPLC method; solubility

Cocrystals, salts, and supramolecular gels of nonsteroidal anti inflammatory drug niflumic acid - Mittapalli, Sudhir; Mannava, M. K. Chaitanya; Sahoo, Rasmita; Nangia, Ashwini (Crystal Growth & Design, 2019)
Niflumic acid (NFA) is a nonsteroidal anti-inflammatory drug (NSAID) classified under the BCS (Biopharmaceutical Classification System) Class II category of poor aqueous solubility and high permeability. In an attempt to improve the physicochemical properties of NFA, particularly solubility and dissolution rate by cocrystallization and salt formation, cocrystals of NFA were prepared with caprolactam (CPR, 1:1) and 2-hydroxy pyridine (2HP, 1:1) as well as salts with piperazine (PIP, 1:0.5), benzenesulfonic acid (BSA, 1:1), benzyl amine (BZA, 1:1 and 2:2), and tyramine (TYA, 1:1). The new solid forms were characterized by powder X-ray diffraction, infrared spectroscopy, and differential scanning calorimetry and confirmed by single crystal X-ray diffraction. In the cocrystals NFA CPR and NFA-2HP, the cyclic amide of the coformer forms a dimer synthon through N-H center dot center dot center dot O hydrogen bonds and such dimers extend through O-H center dot center dot center dot O hydrogen bonds. In piperazine, benzyl amine, and tyramine salts, proton transfer occurs from the NFA to the basic nitrogen of the coformer, and in NFA BSA salt, the proton is transferred from benzenesulfonic acid to the pyridine nitrogen of NFA. In addition to the above salts and cocrystals, supramolecular gels of NFA-PIP and NFA-BZA salts are reported, which were obtained from nitrobenzene, methyl salicylate, menthol, and mesitylene solvents. These gels were studied by rheology. Solubility and dissolution rate of the novel solid forms (NFA CPR, NFA PIP, NFA BSA, and NFA TYA) in 20% EtOH water showed the best behavior for NFA-TYA salt with improvement of 42-and 54-times in solubility and dissolution rate compared to the reference drug. The remaining solids such as NFA-PIP, NFA-BSA salts, and NFA-CPR cocrystal exhibited improvement of 39-, 18-, 1.4-times in solubility and 7.8-, 10-, 2-times for dissolution rate.